Polination methods and seed formation in persimmon trees - Tombolato, Antonio Fernando Caetano (Pesquisa Agropecuaria Brasileira, 2014)
In the Persimmon Breeding Program of the Instituto Agronômico de Campinas (IAC), Campinas, SP, Brazil, several intervarietal crosses of persimmon trees (Diospyros kaki, L.) were made in five different ways, including pollination control under natural conditions. With the objective of calculating the influence of each treatment on seed production, the manipulated flowers, fruits, and seeds were counted. The developing stage of flower and pollen quality influenced the number of seeds produced, much higher than the production under natural conditions. The rate of fecundation is improved when the pollen is applied on the receptive stigma of the open flower, contrary to the method of controlled crosses, applied previously, which consists on removing the petals of floral buds unopened and applying the pollen on the stigma, resulting in reduced seed formation. It was observed that in the absence of pollination the flowers without petals can fructify, but by parthenocarpy, since a large part of the fruits produced do not show any seeds.